IMPLEMENTATION OF E-NOTICE BOARD - C.Anuradha, Garlapati Hema Saikrishna, L Ganeshraj (International Journal of Modern Agriculture, 2021)
Android based College Notification system to provide college related notices directly on your android device. By using this, Staff meeting related notices and student get experiment, tutorial online. The main aim is to replace the traditional notice board with E-notice board. So there is no need to maintain numbers of account for sharing information, exchange of notes and all college related news, then it will be accessible anywhere anytime just on a single click on your android device. Just install “E-Notice Board App” on your android device and you can access all notices of your college. We have developing for staff add notes, experiments dates, submission and for students upload and download tutorials, experiments, question paper and notes in an easy and efficient manner. This project includes major activity entities: add notices, add staff record, and add student record which is handled by Admin. The Admin can add, delete, and update them simultaneously on the online system. These can then be viewed by the students.